Phytoremediation of Metals in Industrial Sludge by Cyperus Kyllingia-Rasiga, Asystassia Intrusa and Scindapsus Pictus Var Argyaeus Plant Species - Abdul Latiff, Ab. Aziz; Abd. Karim, Ahmad Tarmizi; Ahmad, Ahmad Shukri; Ridzuan, Mohd Baharudin; Yung-Tse, Hung (International Journal of Integrated Engineering, 2012)
Laboratory studies have shown phytoremediation is a feasible method for remediating sludge contaminated with heavy metals. This research focused on the ability of plants to hydroponically treat digested industrial sludge contaminated with aluminium (Al), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), nickel (Ni), manganese (Mn) and zinc (Zn). The sludge used in the study was obtained from the wastewater treatment lagoon of a textile factory. Three species were used in the phytoremediation process. They were Cyperus Kyllingia-Rasiga, Asystassia Intrusa and Scindapsus Pictus Var Argyaeus. These species were planted in hydroponic pots placed under a transparent roof to allow natural light. In the first batch, pots containing 2 seedlings of each plant were applied with 9.81 mg, 12.83 mg, 15.85 mg, 18.87 mg and 21.9 mg digested dried industrial sludge. In the second batch, the pots planted with 1, 2, 3, 4 and 5 seedlings and were applied with the same amount of 21.9 mg of digested industrial sludge each. The pH and electrical conductance (EC) of hydroponic solution were monitored in this phytoremediation processes. The results showed that the absorption of heavy metals by Asystassia Intrusa was in the order of Mn > Al > Cu > Fe > Ni > Zn > Cd > Pb > Cr, with medium pH and EC of 6.90 ± 0.73 and 2.47 ± 1.96 μS/cm respectively . The absorption of heavy metals by Cyperus Kyllingia-Rasiga was in the order of Mn > Cu > Ni > Cr > Pb > Zn > Fe > Al > Cd at medium pH 6.87 ± 0.71 and EC 2.72 ± 1.85 μS/cm and the absorption by Scindapsus Pictus Var Argyaeus was in the order of Cu > Ni > Mn > Pb > Zn > Cr > Cd > Al > Fe at neutral pH and the EC 2.72 ± 1.71 μS/cm. From the study it was concluded that the plant species used were able to significantly absorb the metals present in industrial sludge.